ANALISIS EVALUATIF KEBIJAKAN SEKOLAH DALAM MENINGKATKAN KOMPETENSI LULUSAN SISWA SMK MUHAMMADIYAH 2 PLAYEN YOGYAKARTA - Nurul Faiqah (Jurnal Ilmiah Didaktika, 2018)
This article attempts to describe the "true tangle" between school policy at the level of idealism with the progress and commemoration of the competence of school leavers in the field of praxis in the field. This research takes place in SMK Muhammadiyah 2 Playen, Yogyakarta. Based on the evaluative analysis in the school showed that; 1) Generally, The formulation of school policy can be said to support the improvement of competency standards of graduate students SMK Muhammadiyah 2 Playen. The formulation of policy (policy making) is done through deliberation or work meeting of leaders and teachers. Judging from the form aktivnnya, then the policy is in the form of academic and non academic activities. 2) at the level of policy implementation, the policy implementers themselves come from the highest levels to the lowest levels such as head master, teachers, staffs, and students. Implementation is certainly through the process of communication and socialization with the target of school policy. the implementation of school policies on the way and the process of course encountered obstacles and challenges. The point that support the implementation of school programs are consistency of school residents, acceptance and participation of school residents and communication. While the obstacles and challenges of implementation of the policy include; lack of potential sources of schools; low student learning motivation; limited economic parent; and the low awareness of teachers. 3) Evaluation of school policy. As for those who act as evaluators of school policies are those who are involved in the formulation and implementing of school policies, especially principals and teachers.